Inibição nitrérgica local favorece o processo de regeneração do tendão de aquiles em ratos submetidos à tenotomia - MORAES, Suellen Alessandra Soares de (Universidade Federal do Pará, 2017)
The tendon injuries prevalence has been increased usually by repetitive movements in the occupational and recreational activities of society. The main features this injury involve healing dysfunction and loss of extracellular matrix. At this tissue, the extracellular matrix is basically made of type I collagen and the loss of this protein associated with problems in the remodeling have been considered the major responsible for the symptomatic and functional effects of injury. Additionally the literature reports the nitric oxide synthase expression was up-regulated throughout the repair process. At this context the propose of this work is investigated the nitrergic local inhibition in tissue and functional recovery after tendon injury. We used a experimental model of Achilles tendon rupture for establish pathophysiological changes similar to chronic tendinopathy. The animals were divided into experimental groups control, injury+vehicle (saline, 0,9%), injury+L- Nω-nitro-L-arginine methyl ester (L-NAME, 5mM) and injury+sodium nitroprusside (SNP, 3mM), which were followed until the 21º day, when were killed to collect samples. In order to access nitric oxide production Griess nitrite assay was used. Functional recovery was calculated by Achilles Functional Index (AFI) in 0, 7, 14 and 21 days. Tendons were also processed for histomorphological and autofluorescence analysis. The body weight gain was also evaluated. We characterized the effect of drugs about tissue without stronger systemic influences by maintenance of body weight and plasmatic levels of nitrite. The L-NAME led to significant decrease in the cellular density, vessel formation between collagen network, accelerated the tissue organization and restored early the functional pattern at 21 days after injury. On the other hand, the treatment with SNP and vehicle remained the tissue disorganization and low functional performance. Taken together our results suggest a positive effect of local suppression of NOS after rupture for tissue remodeling, contributing to tendon regeneration.